(0 0 0) and (0 1 0) energy levels of the HD18O and D218O molecules from analysis of their v2 bands - Liu A.-W. An-Wen; Song K. F. Ke-Feng; Ni H.-Y. Hong-Yu; Hu S.-M. Shui-Ming; Naumenko O. V.; Vasilenko I. A.; Mikhailenko S. N. Semen Nikolaevich (2011, 2011)
Title screen